Differential performance in height growth rate and yield components to enhance cane yields of various sugarcane types during early drought and post-recove - Kulrat, Thanakorn; Jongrungklang, Nakorn; Vorasoot, Nimitr; Puangbut, Darunee; Jira-Anunkul, Weeraphorn; Songsri, Patcharin (Agriculture and Natural Resources, 2025)
Importance of the work: Drought stress reduces sugarcane yields. A deeper understanding of the growth and yield components across different sugarcane genotypes could improve the process of breeding sugarcane with tolerance to drought. Objectives: To investigate the effects of various water regimes on the growth behavior, yield components and cane yield of different sugarcane genotypes. Materials and Methods: The experiment was designed as a split plot in a randomized complete block design with three replications. The main plot involved two water regimes—(well-watered (WW) and early drought stress (DS) —during 2–6 mth after tillering (MAT; tillering and early stalk elongation phase). The subplot contained six diverse sugarcane genotypes. The stalk height was measured at 3, 6, 8, 10, and 12 MAT. The height growth rate (HGR) and stalk number per stool were recorded at 6, 8, 10, and 12 MAT. The cane yield and yield components were collected at harvest. Results: Early drought reduced the cane yield, stalk length, single stalk weight and millable cane. Based on the cane yield, F03-362 (F1), KK09-0358 (BC1) and KK3 (commercial cane) were identified as drought-resistant genotypes. The high number of millable canes and plant height were important traits that promoted high cane yield in F03-362, while KK09-0358 and KK3 were derived from a medium number of millable canes and a high single stalk weight. Main finding: HGR, during recovery periods (re-watered after 6 MAT until 12 MAT), impacted promoting cane yield. The drought-tolerant genotypes had greater values for HGR than the drought-susceptible genotypes. This perspective was beneficial as it emphasized the selection characteristics in sugarcane breeding efforts to enhance drought tolerance.